The differences between the winning and losing team anxiety level and self - confidence in the Malaysia final fa cup 2016. Mazlan Ismail and Sharina Salmi Azmi - Ismail, Mazlan; Azmi, Sharina Salmi (Faculty of Sports Science and Recreation, 2017)
This study had tried to compare the difference between the winning and losing team’s anxiety level and self- confidence in the Malaysia Final FA Cup 2016. Thirty six male football players aged between 23 to 36 years (M = 28.58, SD = 3.38), with 5 to 18 years of experience had participated in this study. All players were purposively chosen from the finalist FA Cup 2016 Johor Darul Takzim (JDT) team and PKNS FC team. The Competitive State Anxiety Inventory-2R (CSAI-2R) questionnaire was used in this study and was given prior to the competition. The result clearly showed that the winning team had low level of anxiety and high level of self- confidence compared to the losing team. Anxiety and selfconfidence were important because it can predict the performance of the athletes. Hence, psychological skills training can be considered by coaches and sport psychologist during practice and competition in order to improve the performance of athletes.